Clinical Features, Radiological Characteristics, and Outcomes of Patients With Intracranial Alveolar Echinococcosis: A Case Series From Tibetan Areas of Sichuan Province, China - Li, Sisi; Chen, Jiani; He, Yongqiao; Deng, Yongyi; Chen, Jie; Fang, Wenyu; Zeren, Zhamu; Liu, Yadong; Abdulaziz, Ammar Taha Abdullah; Yan, Bo; Zhou, Dong (Frontiers in Neurology, 2021)
Objectives: Intracranial alveolar echinococcosis (IAE), a zoonotic disease, is a critical health problem in the Tibetan region. We aimed to describe the clinical and radiological characteristics and outcomes among patients with IAE. Methods: We screened patients diagnosed with IAE between March 2015 and May 2019 at the Ganzi Tibetan Autonomous Prefecture People’s Hospital. Detailed demographics, clinical characteristics, neuroimaging features, and outcomes were recorded. Results: A total of 21 patients with an average age of 44.1 ± 12.7 years were included. Thirteen (61.9%) patients were male. The most common chief neurological complaint was headache (n=17, 81.0%), followed by dizziness, seizure, visual disturbances, hemiparesis, disturbed consciousness, and dysphasia. All the patients had coexisting liver localizations. The typical neuroimaging features of IAE on cerebral magnetic resonance imaging scans showed obvious low-signal shadow with multiple small vesicles inside the lesions on T2-weighted images and FLAIR images. The pathological HE staining demonstrates vesicular lesions with several internal sacs. For hepatic alveolar echinococcosis (AE), the hepatic portal was invaded in six (28.6%) patients, and the portal vein (n=5, 23.8%) was the mostly commonly involved vessel. As for treatment, eleven patients (52.4%) had poor compliance with albendazole. The duration of patients taken albendazole ranged from 2 months to 3 years. Cerebral AE surgery was performed in eleven patients, five of them underwent partial resection of AE lesions, and six patients received total resection. One patient with primary IAE underwent radical surgery. Ten patients (47.6%) died during the follow-up for a mean of 21.7 ± 11.9 (3-46) months. In total, 28.9% of the patients died within 5 years, and 71.6% died within 10 years. The median interval between the date of diagnosis as AE and death was 84 (19-144) months. Conclusion: Despite substantial advances in diagnostic and therapeutic methods, the treatment of IAE remains difficult and results in unsatisfactory outcomes. The major critical issue is surgical treatment of IAE although the disease is disseminated. Besides, lifelong albendazole would be indicated, but most patients had poor medication compliance. It is important to educate patients about the necessity of medical treatment.